Total synthesis of (+/-)/(+)-subincanadine E and determination of absolute configuration - Kalshetti, Manojkumar G.; N. P. Argade (Journal of Organic Chemistry, 2017)
A facile synthesis of (+/-)-subincanadine E was described from tryptamine-based maleimide. 1,2-Addition of Grignard reagent to maleimide, internal activation of formed lactamol for in situ 1,4-addition of Grignard reagent, and associated position-specific allylic rearrangement in diastereoselective Pictet-Spengler cyclization were the key steps. Enantioselective first total synthesis of naturally occurring cytotoxic (+)-subincanadine E was also accomplished from (S)-acetoxysuccinimide via an unusual syn-addition of cuprate to the alpha/beta-unsaturated lactam. Sinister absolute configuration was assigned to (+)-subincanadine E on the basis of total synthesis. (S)-Acetoxy group in the succinimide precursor was initially employed to impart regio- and stereoselectivity and then as a suitable leaving group to generate the desired conjugated lactam.

Regioselective and stereoselective reductive aziridinium ring cleavage leading to azabicyclodecane architecture: enantioselective synthesis of (+)-subincanadine F - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Journal of Organic Chemistry, 2018)
Enantioselective synthesis of cytotoxic indole alkaloid (+)-subincanadine F was accomplished starting from the corresponding (S)-acetoxysuccinimide via aziridinium ring formation and its reductive ring expansion route. Regioselective and stereoselective reductive aziridinium carbon-nitrogen bond cleavage comprising ring expansions was a key step. The (S)-OMOM protection of the hydroxyl moiety adjacent to a benzylic carbon of an in situ formed aziridinium system was necessary for lithium borohydride-induced reductive ring expansions, and it also served as a latent source of an essential ketone carbonyl group for the generation of an alpha,beta-conjugated system.

Progress in total synthesis of subincanadine alkaloids and their congeners - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Organic & Biomolecular Chemistry, 2019)
A concise account of isolation, characterization, bioactivity, plausible biogenetic pathways, and most importantly, total synthesis of structurally fascinating and biologically imperious indole-based subincanadine alkaloids and their biogenetic congeners are described in the present review with special emphasis on total synthesis and therein an involved set of key reactions.

Stereoselective synthesis of subincanadine alkaloids framework - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
Starting from, N-tosyltryptamine and (S)-acetoxysuccinic anhydride, a facile synthesis of (-)-indolizinoindolone has been demonstrated as a basic structural outline of bioactive subincanadine alkaloids. Regioselective Grignard reaction with (S)-acetoxysuccinimide, stereoselective intramolecular cyclization to form (-)-indolizinoindolone skeleton and TiCl4 induced condensation with acetaldehyde for stereoselective generation of exocyclic carbon carbon double bond are the key features.
Keywords: (S)-Acetoxysuccinimide; alane reduction; condensation; Grignard reaction; indolizinoindolone; PCC-oxidation; stereoselective Pictet-Spengler cyclization